2023
DOI: 10.3390/ijns9020031
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Fabry Disease: Current Status of Knowledge

Vincenza Gragnaniello,
Alessandro P. Burlina,
Anna Commone
et al.

Abstract: Fabry disease is an X-linked progressive lysosomal disorder, due to α-galactosidase A deficiency. Patients with a classic phenotype usually present in childhood as a multisystemic disease. Patients presenting with the later onset subtypes have cardiac, renal and neurological involvements in adulthood. Unfortunately, the diagnosis is often delayed until the organ damage is already irreversibly severe, making specific treatments less efficacious. For this reason, in the last two decades, newborn screening has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 101 publications
(153 reference statements)
2
3
0
Order By: Relevance
“…The two female newborns were found to be false positives (overall PPV 90%). The overall incidence of α-GalA deficiency was 1:8879 (1:4121 males), which is similar to previous reports from NBS programs [59], but higher than the clinically estimated incidence (1:40,000) [60], probably due to the recognition of previously undiagnosed later-onset forms of FD. Ten patients carried unclassified variants.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The two female newborns were found to be false positives (overall PPV 90%). The overall incidence of α-GalA deficiency was 1:8879 (1:4121 males), which is similar to previous reports from NBS programs [59], but higher than the clinically estimated incidence (1:40,000) [60], probably due to the recognition of previously undiagnosed later-onset forms of FD. Ten patients carried unclassified variants.…”
Section: Discussionsupporting
confidence: 86%
“…In the USA, FD is not included in the RUSP, but local laws promoted by NBS advocates and parents allowed its implementation in NBS in several states. These programs confirmed the high incidence of the disease (1:1790 to 1:15,558), but also the high number of false positives [ 59 ]. Conversely, in Taiwan, NBS for FD was started in 2006.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Recently, pilot NBS programs for Fabry disease (FD) have been implemented worldwide to explore the potential inclusion of this disease in national programs in Europe [ 2 , 3 ], Japan [ 4 ], China [ 5 ], and the USA [ 6 ]. These results have shown that FD is surprisingly more common than previously considered [ 7 ]. FD is associated with lysosomal glycohydrolase α-galactosidase A (GLA) deficiency, which causes premature death due to cardiovascular disease, kidney failure, and strokes, if not treated from birth with the recommended enzyme replacement therapy [ 8 , 9 ].…”
Section: Introductionsupporting
confidence: 54%
“…FD is associated with lysosomal glycohydrolase α-galactosidase A (GLA) deficiency, which causes premature death due to cardiovascular disease, kidney failure, and strokes, if not treated from birth with the recommended enzyme replacement therapy [ 8 , 9 ]. The methods used for pilot NBS programs for FD are based on fluorometry, digital microfluidics, tandem mass spectrometry, and immune quantification and are discussed in detail in the review by Gragnianiello and colleagues [ 7 ]. However, despite the variety of methods currently available for the diagnosis of this disease, for the widespread dissemination of newborn screening, it is necessary to improve the cost of analysis, accuracy, parallelism, and extraction of information from a limited amount of biological material.…”
Section: Introductionmentioning
confidence: 99%